A history of modern psychology - Schultz, Duane P.; Schultz, Sydney Ellen (Belmont, CA Thomson Higher Education, 2008)
Focusing on modern psychology, the text's coverage begins with the late 19th century. The authors personalize the history of psychology not only by using biographical information on influential theorists, but also by showing how major events in those theorists' lives have affected the authors' own ideas, approaches, and methods.
The study of the history of psychology -- Philosophical influences on psychology -- Physiological influences on psychology -- The new psychology -- Structuralism -- Functionalism : antecedent influences -- Functionalism : development and founding -- Applied psychology : the legacy of functionalism -- Behaviorism : antecedent influences -- Behaviorism : the beginnings -- Behaviorism : after the founding -- Gestalt psychology -- Psychoanalysis : the beginnings -- Psychoanalysis : after the founding -- Contemporary developments in psychology.
International student edition.
Includes bibliographical references (pages 524-548) and indexes.
Keywords: Psychology -- History -- Textbooks